2022
DOI: 10.7759/cureus.32082
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predictors of Mortality in COVID-19 Myocardial Injury: The Role of Troponin Levels, GRACE Score, SOFA Score, and TIMI Score

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) infection is associated with troponin elevation, which is associated with increased mortality. However, it is not clear if troponin elevation is independently linked to increased mortality in COVID-19 patients. Although there is considerable literature on risk factors for mortality in COVID-19-associated myocardial injury, the Global Registry of Acute Coronary Events (GRACE), Thrombolysis in Myocardial Infarction (TIMI), and Sequential Organ Failure Assessment (SOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Cycloheximide (5-HT2A and 5-HT 2 B antagonists) administered after lower extremity MI reduced 5-HT levels while preventing valvular fibrotic remodeling was associated with increased mitral valve size and reduced mitral regurgitation (38). Additionally, SOFA score was an independent predictor of mortality in patients with myocardial injury (39). In this study, lower SOFA and SAPS II scores were observed in the OND-medication group, indicting OND might exert its protective effect through relieving disease severity in patients with MI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cycloheximide (5-HT2A and 5-HT 2 B antagonists) administered after lower extremity MI reduced 5-HT levels while preventing valvular fibrotic remodeling was associated with increased mitral valve size and reduced mitral regurgitation (38). Additionally, SOFA score was an independent predictor of mortality in patients with myocardial injury (39). In this study, lower SOFA and SAPS II scores were observed in the OND-medication group, indicting OND might exert its protective effect through relieving disease severity in patients with MI.…”
Section: Discussionmentioning
confidence: 99%
“…In the matched cohort, in-hospital mortality (5.7% vs 8.0%), 28-day mortality (7.8% vs 10.8%), and 90-day mortality (9.2% vs 12.5%) rates were significantly lower in patients treated with OND. In terms of disease severity, there were lower SOFA (35(28-43) vs. 36 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)) and SAPS II (4(2-6) vs. 4(2-7)) in the OND-medication group.…”
Section: Clinical Outcomes After Psmmentioning
confidence: 96%
See 1 more Smart Citation
“…In practice, postoperative TIMI blood flow was a separate predictor of in-hospital mortality in SARS-CoV-2-positive patients, consistent with previous reports on STEMI patients. [ 38 ] The interaction between inflammation, thrombogenic factors, and others may influence the efficacy of refusion in the coronary artery of STEMI patients, subsequently affecting the outcomes of patients.…”
Section: Discussionmentioning
confidence: 99%